Kemenarikan Objek Wisata Instagram Dalam Perencanaan Pariwisata - Mayang Fitri, Ebtana Sella; Wijaya, Ridho Gata (Jurnal Pariwisata Terapan, 2023)
The development of Instagram tourism objects in various parts of the world has encouraged many tourists to compete with each other to visit the place. Based on previous studies, it was stated that most of the visitors from this Instagram tourist attraction were millennials. In terms of terminology, Instagram tourism attraction is a tourist destinations which have unique, exist, and hits characters. It also used and utilized as photo hunting objects to share on Instagram accounts. The high interest of millennial tourists to produce and get the good photos has encouraged the development of similar Instagram tourism attraction. According to Gunn (1993), tourist destinations can attract tourist visits if it have several components such as attractions, services, information, promotions and transportation. However, these components are not the main focus in planning and developing Instagram tourism. The purpose of this article is to try to analyze the attractiveness of Instagram tourism attraction and it can be used as a reference in planning the management of Instagram tourism objects. This article used a qualitative method by using secondary data sources which are collected from several scientific articles, books, statistical data, and newspaper media. The results of this article found that the attractiveness of Instagram tourism attraction is actually a tourist activity that solely wants to pursue visual pleasure because the character of this attraction type is a blurry attraction. Therefore, planning of the development of Instagram tourism attraction must consider the components that can encourage to creating/producing good visual quality.